2023
DOI: 10.3390/jcm12113745
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Manifestations of Takayasu’s Arteritis—A Case-Based Systematic Review and Meta-Analysis

Abstract: Takayasu’s arteritis (TA) is a type of vasculitis in which inflammation develops in large vessels, especially in the aorta and its branches. Our study aims to determine the prevalence and type of ocular manifestations in TA. A systematic literature search was conducted in December 2022 using three electronic databases (PubMed, Scopus, and Web of Science). The following data were extracted from each article: the name of the first author; the patient’s age, sex, and origin (continent); circumstances connected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 113 publications
0
0
0
Order By: Relevance
“…Between 10% and 20% of patients diagnosed with PN develop ophthalmic or neuro-ophthalmic signs and symptoms, whereas in the case of Kawasaki disease (KD), the presence of eye disorders reaches 90% [8,9]. Our findings, described in a systematic review and meta-analysis focusing on ocular manifestations of TA, revealed that in over 74% of the analyzed cases (122 patients), ophthalmic pathologies preceded the diagnosis of TA [10]. Although the association between primary vasculitis and ocular manifestations is well-known, routine ophthalmological examinations for patients with these diseases seem to be lacking, despite the potential for systemic inflammation and ischemia to lead to severe ophthalmic complications.…”
Section: Introductionmentioning
confidence: 62%
“…Between 10% and 20% of patients diagnosed with PN develop ophthalmic or neuro-ophthalmic signs and symptoms, whereas in the case of Kawasaki disease (KD), the presence of eye disorders reaches 90% [8,9]. Our findings, described in a systematic review and meta-analysis focusing on ocular manifestations of TA, revealed that in over 74% of the analyzed cases (122 patients), ophthalmic pathologies preceded the diagnosis of TA [10]. Although the association between primary vasculitis and ocular manifestations is well-known, routine ophthalmological examinations for patients with these diseases seem to be lacking, despite the potential for systemic inflammation and ischemia to lead to severe ophthalmic complications.…”
Section: Introductionmentioning
confidence: 62%
“…A study by Pasko et al noted ocular manifestations presenting prior to diagnosis of Takayasu arteritis in 74.6% of cases [3]. This may be explained by cases in which initial manifestations included constitutional symptoms that were non-specific.…”
mentioning
confidence: 99%
“…Ocular manifestations of Takayasu arteritis can be seen in a wide range of 8.1-68% of the patients (1). Apart from two case based systematic reviews, current literature is lacking in describing extent of ocular involvement in Takayasu arteritis (1,3). Current classification of Takayasu arteritis does not include visual changes and consequently no ophthalmological examination is recommended even after diagnosis and ocular manifestations can go unnoticed.…”
mentioning
confidence: 99%